Adherence to clinical guidelines for the evaluation and management of eosinophilic esophagitis among gastroenterologists in the Arab countries - Al-Hussaini, Abdulrahman; Alrashidi, Jaber; Miqdady, Mohamad; Bitar, Rana; AlFayyad, Isamme (Frontiers in Pediatrics, 2025)
BackgroundThe practice patterns of eosinophilic esophagitis (EoE) remain poorly characterized. Few studies investigated the variability of clinical patterns among gastroenterologists, mainly in the United States.ObjectivesWe assessed the practice patterns of gastroenterologists in the Arab countries regarding the diagnosis and management of EoE, and their concordance with the European 2017 guidelines and the Proceedings of the AGREE Conference published in 2018.MethodsWe conducted a cross-sectional, self-administered, online survey of practicing gastroenterologists in the Arab countries (April to December 2022). The survey consisted of 23 questions and was designed to assess the respondents’ practice characteristics, knowledge and practice on diagnosis and treatment of EoE.ResultsA total of 190 participants responded to the survey (118 pediatric gastroenterologists and 72 adult gastroenterologists). Thirty-six percent and 31% saw ≥6 new patients with EoE annually, 55% were ‘very familiar’ with the most recent EoE guidelines, and 49% attended ≥3 E-E-related educational activities during the 3 years prior to the survey. The majority of the respondents (72%) did not require a trial of a proton-pump inhibitor (PPI) prior to making the diagnosis of EoE and 66% obtain biopsies from multiple esophageal levels. While 90% of the respondents considered eosinophil-predominant inflammation on esophageal biopsies necessary for the diagnosis of EoE, only 27% felt that symptoms of esophageal dysfunction are necessary for the diagnosis, and only half of the participants considered exclusion of other etiologies of esophageal eosinophilia necessary for the diagnosis of EoE. For first-line treatment, only 16% used PPI monotherapy, 12.6% topical steroids, and 63.5% treat with a variable combination of PPIs, topical steroids, and dietary elimination. Sixty percent would repeat upper endoscopy to determine histologic improvement and 72% use maintenance therapy in responders. Compared to pediatric gastroenterologists, significantly fewer adult gastroenterologists reported taking biopsies from proximal and distal esophagus (34% vs. 66%) and gastric and duodenal biopsies (67% vs. 90%) when EoE was suspected (P < 0.001).ConclusionThere is significant variability in adherence to EoE guidelines among gastroenterologists in the Arab countries. Our results highlight areas of need for continuous education and form the basis to assess implementation efforts in the future.